Upgrading the Organic Fraction of Municipal Solid Waste by Low Temperature Hydrothermal Processes - Sailer, Gregor; Knappe, Victoria; Poetsch, Jens; Paczkowski, Sebastian; Pelz, Stefan; Oechsner, Hans; Bosilj, Monika; Ouardi, Siham; Müller, Joachim (Energies (Basel), 2021)
In comparison to lignocellulosic biomass, which is suitable for thermo-chemical valorization, the organic fraction of municipal solid waste (OFMSW) is mainly treated via composting or anaerobic digestion (AD). An efficient utilization of OFMSW is difficult due to variations in its composition. Based on the characteristics of OFMSW, hydrothermal treatment (HTT) experiments at temperatures < 200 °C as an alternative OFMSW-processing were evaluated in this study. The raw OFMSW was characterized with a dry matter (DM)-based organic dry matter (oDM) content of 77.88 ± 1.37 %DM and a higher heating value (HHV) of 15,417 ± 1258 J/gDM. Through HTT at 150, 170 and 185 °C, the oDM contents as well as H/C and O/C ratios were lowered while the HHV increased up to 16,716 ± 257 J/gDM. HTT led to improved fuel properties concerning ash melting, corrosion stress and emission behavior. Negative consequences of the HTT process were higher contents of ash in the biochar as well as accumulated heavy metals. In the sense of a bioeconomy, it could be beneficial to first convert raw OFMSW into CH4 through AD followed by HTT of the AD-digestate for the generation of solid fuels and liquid products. This could increase the overall utilization efficiency of OFMSW.